PENGEMBANGAN TEKNOLOGI SINGLE SIGN ON BERBASIS CAS-LDAP DI UNIVERSITAS BINA DARMA - Kunang, Yesi Novaria; Yadi, Ilman Zuhri (Universitas Bina Darma, 2014)
Universitas Bina Darma has many systems and applications used by students, faculty and staff at the University. The number of systems and applications that are used provide an obstacle for users to remember the username and password to log on each of these systems. In addition, the admin should manage all users that exist in each of the distributed system, so that if a user no longer active in an application or in the entire system, then the admin should make changes to the user data in each system. For this study aims to develop a prototype of a secure single sign-on and can be implemented at the University of Bina Darma that integrate elearning systems, blogs and mail servers. With the developed system allows the users only need to log on to one of the three systems.